Biologically controlled mineralization in the hypercalcified sponge Petrobiona massiliana (Calcarea, Calcaronea) - Gilis, M.; Baronnet, A.; Dubois, P.; Legras, L.; Grauby, O.; Willenz, P. (Journal of Structural Biology, 2012)
Hypercalcified sponges, endowed with a calcium carbonate basal skeleton in addition to their spicules, form one of the most basal metazoan group engaged in extensive biomineralization. The Mediterranean species Petrobiona massiliana was used to investigate biological controls exerted on the biomineralization of its basal skeleton. Scanning and transmission electron microscopy (SEM, TEM) confirmed that basopinacocytes form a discontinuous layer of flattened cells covering the skeleton and display ultrastructural features attesting intense secretory activity. The production of a highly structured fibrillar organic matrix framework by basopinacocytes toward the growing skeleton was highlighted both by potassium pyroan?timonate and ruthenium red protocols, the latter further suggesting the presence of sulfated glycosami?noglycans in the matrix. Furthermore organic material incorporated into the basal skeleton was shown by SEM and TEM at different structural levels while its response to alcian blue and acridine orange staining might suggest a similar acidic and sulfated chemical composition in light microscopy. Potassium pyroantimonate revealed in TEM and energy electron loss spectroscopy (EELS) analysis, heavy linear precipitates 100–300 nm wide containing Ca2+ and Mg2+ ions, either along the basal cell membrane of basopinaco?cytes located toward the decalcified basal skeleton or around decalcified spicules in the mesohyl. Based on the results of the previous mineralogical characterization and the present work, an hypothetical model of biomineralization is proposed for P. massiliana: basopinacocytes would produce an extracellular organic framework that might guide the assemblage of submicronic amorphous Ca- and Mg-bearing grains into higher structural units.